A fluorinated block copolymer and a preparation method thereof
By synthesizing fluorine-containing block copolymers, using their automatic migration and winding effects at high temperatures, the problem of fluorine-containing materials being easily decomposed under high temperature conditions is solved, and the material is efficient anti-fouling and good adhesion is achieved.
Patent Information
- Application Number
- CN202310109541.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-08
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-02-08
AI Technical Summary
Currently, fluorine-containing materials are easy to decompose under high temperature conditions, which is difficult to meet the processing needs of material forming.
By synthesizing fluorine-containing block copolymers, the long fluorine-alkyl and long-chain alkyl structures are grafted with pentafluorostyrene, the obtained fluorine-containing block copolymers are automatically migrated to the surface enrichment at high temperatures, and are wound with long-chain alkane groups and substrate molecules to improve the adhesion and antifouling properties of the material.
It achieves good thermal stability, mechanical properties and processing properties under high temperatures, and improves the anti-fouling durability of the material and adhesion to the substrate.
Smart Images

Figure CN116217841B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fluorine-containing additives, in particular to a fluorine-containing block copolymer and a preparation method thereof. Background Art
[0002] Fluoropolymers have a prominent position in the design of materials with special functions, specific chemical and physical properties due to their high heat resistance, chemical resistance, aging resistance, oleophobicity and excellent inertness. At the same time, due to the low polarizability, strong electronegativity and high CF bond energy (540kJ / mol) of fluorine, fluorine-containing polymers are superior to other polymers in many properties, and are widely used in the fields of petrochemical, aerospace, automobile, textile industry and medical materials.
[0003] At present, researchers obtain hydrophobic and oleophobic materials mainly by functionalizing the surface of the material through coating technology, that is, covering the surface of the material with a layer of low surface energy resin to give the surface of the material hydrophobic and oleophobic properties to achieve anti-fouling effects. Among these hydrophobic and oleophobic materials, fluorinated polymers are mostly used as coatings in various fields because of their good hydrophobic and oleophobic properties. However, the low surface energy properties of fluorinated coatings result in poor adhesion to the substrate, and they are easy to fall off by themselves during long-term use or when subjected to external friction.
[0004] Current methods for improving the adhesion between fluorine-containing coatings and substrates include multi-layer coating, chemical blending, and the preparation of fluorine-containing self-stratifying coatings. Self-stratifying coatings are made by blending and coating two or two incompatible polymers, which spontaneously undergo phase separation during the film-forming process to form a continuous multi-coating system. However, the self-stratifying coating and the substrate are mainly bonded through penetration, with weak forces, and there is very little entanglement between the polymer chain segments. After long-term use or friction, it is still easy to fall off the main material.
[0005] Therefore, low surface energy fluorine-containing polymers can be introduced during the material molding process by means of blending. The direct fusion method through the molding process can greatly improve the interaction between the fluorine-containing coating and the substrate. At the same time, the melting process is conducive to the spontaneous migration of the fluorine-containing material to the surface of the material, ensuring the long-term anti-fouling effect of the material. In order to meet the processing requirements in material molding, the introduced fluorine-containing polymer should have a good processing structure, no decomposition at high temperature, no cross-linking, and good rheological properties. Fluorine-containing acrylate polymers, which are currently widely used in fluorine-containing coatings, are easily degraded under high temperature conditions because of the ester bonds in their molecular structure. At the same time, due to their low surface energy, fluorine-containing polymers undergo microphase separation when blended with other polymers, causing serious damage to the mechanical properties of the material; thus, it is difficult to meet the aforementioned processing requirements. Summary of the invention
[0006] <Technical Problems Solved by the Invention>
[0007] It is used to solve the problem that current fluorine-containing materials are easy to decompose under high temperature conditions and are difficult to meet the processing requirements of material molding.
[0008] <Technical solution adopted by the present invention>
[0009] In view of the above technical problems, the object of the present invention is to provide a fluorinated block copolymer and a preparation method thereof.
[0010] The present invention uses pentafluorostyrene grafted with long fluoroalkyl and long chain alkyl structures to synthesize two modified monomers respectively, and the prepared fluorinated block copolymer is obtained. Through the "self-stratification" effect of the long fluorine chain segment automatically migrating to the surface for enrichment at high temperature and the compatibilization effect of the long chain alkane group entangled with the substrate molecule, a long-term antifouling molding material with good surface properties, mechanical properties and processing properties is obtained.
[0011] The specific contents are as follows:
[0012] First, the present invention provides a fluorinated block copolymer having the structural formula:
[0013]
[0014] R F CF3(CF2) m (CH2) n —, m is an odd number from 1 to 7, and n is an integer from 1 to 3;
[0015] R C CH3(CH2) k —, k is an integer from 4 to 12;
[0016] Wherein, i:j=0.5-2, and the value range of i and j is an integer from 10 to 100.
[0017] Second, the present invention provides a method for preparing the above-mentioned fluorinated block copolymer, comprising the following steps:
[0018] S1 In the reaction system, PFS reacts with perfluoro-substituted ethanol to obtain a first modified monomer, and PFS reacts with long-chain alkyl ethanol to obtain a second modified monomer;
[0019] S2 includes an initiator and a catalyst in a reaction system, and the first modified monomer is polymerized by atom transfer radical active polymerization to obtain a macromolecular initiator;
[0020] The S3 macromolecular initiator and the second modified monomer are polymerized to obtain a fluorine-containing block polymer.
[0021] <Beneficial Effects of the Invention>
[0022] (1) The fluorinated block copolymer provided by the present invention has a thermal decomposition temperature of 330-400°C and exhibits good thermal stability during high-temperature processing;
[0023] (2) The present invention can be blended with general plastics (polystyrene, polyethylene, polypropylene, etc.) and the product has good compatibility. While ensuring the mechanical properties, the water-repellent and oil-repellent properties of the blended materials are improved. Compared with the coating process, the present invention exhibits better antifouling durability when used in the molding process. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the H-NMR spectrum of different fluorinated block copolymers;
[0025] Figure 2 This is the contact angle result diagram of the blended materials of different fluorinated block copolymers. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0027] <Technical solution>
[0028] First, the present invention provides a fluorinated block copolymer having the structural formula:
[0029]
[0030] R F CF3(CF2) m (CH2) n —, m is an odd number from 1 to 7, and n is an integer from 1 to 3;
[0031] R C CH3(CH2) k —, k is an integer from 4 to 12;
[0032] Where i:j=0.5~2.
[0033] Preferably, R F CF3(CF2) m (CH2) n —, m is an odd number from 3 to 5, and n is an integer from 1 to 3;
[0034] R C CH3(CH2) k —, k is an integer from 5 to 9;
[0035] Where i:j=1~1.5.
[0036] In the present invention, the value range of i and j is an integer of 10-100, preferably an integer of 10-50.
[0037] Second, the present invention provides a method for preparing the above-mentioned fluorinated block copolymer, and the preparation route thereof is as follows.
[0038]
[0039] The detailed steps of the preparation method are:
[0040] Using ultra-dry tetrahydrofuran (THF) as solvent, PFS is reacted with perfluoro substituted ethanol or long-chain alkyl ethanol in the presence of a strong base M to prepare fluorinated modified pentafluorostyrene monomer (PFSF x ), long chain alkyl modified pentafluorostyrene monomer (PFSC y ) ; using phenethyl bromide (PhEBr) as initiator, xylene (xylene) as solvent, monomer PFSF x Preparation of macroinitiator PFSF via atom transfer radical living polymerization catalyzed by cuprous bromide (Cu(I)Br) and 2,2-bipyridine (bipy) x -Br; by PFSF x -Br and Monomer PFSC y The fluorinated block copolymer is obtained by secondary polymerization.
[0041] In the present invention, the monomers PFSFx and PFSCy are synthesized by nucleophilic substitution at the 4-position of PFS, and the molar ratio of PFS to perfluoro-substituted ethanol (or long-chain alkyl ethanol) is 1 to 1.5:1; the reaction temperature is -10 to 30°C, and the reaction time is 3 to 30 hours.
[0042] In the present invention, the strong base M is selected from at least one of the following: sodium hydride, potassium hydride and calcium hydride.
[0043] In the present invention, the molar ratio of the initiator phenethyl bromide (PhEBr) to cuprous bromide (Cu(I)Br) and 2,2-bipyridine (bipy) is 1:1:3; the reaction temperature is 100-120° C., and the reaction time is 15-30 hours.
[0044] In the present invention, Cu(I)Br, bipy, macromolecular initiator PFSF x -Br and PFSC yThe molar ratio of the substances is 1:1:1~3:200~350; the reaction temperature is 100~120°C, and the reaction time is 15~30h.
[0045] <Example>
[0046] Example 1
[0047] PFS 5.816g (30mmol), perfluorohexylethanol 7.286g (20mmol) and NaH 0.528g (22mmol) were added to a three-necked flask, mixed and dissolved in 60mL THF, and then the reaction was carried out at 0°C and N2 atmosphere for 19h. After the reaction was completed, the obtained reaction mixture was concentrated to remove the solvent, then washed with ice water, extracted with methyl tert-butyl ether, and the water was removed with anhydrous sodium sulfate. After being spin-dried, it was placed in a vacuum oven to dry for 2h, and finally a light yellow oily liquid was obtained, which was PFSF6.
[0048] The same synthesis steps were adopted, except that perfluorohexylethanol was replaced with 2.604 g (20 mmol) of n-octanol as feed material to obtain a light yellow oily liquid, which was PFSC8.
[0049] In a high vacuum reaction tube, add PFSF6 5.813g (10.80mmol), PhEBr 0.126g (0.68mmol), Cu(I)Br 0.097g (0.68mmol) and bipy 0.319g (2.04mmol), mix and dissolve in 5mL xylene. Then use a dry ice-ethanol bath, freeze-vacuum-melt-vacuum cycle 3 times, fully eliminate the dissolved oxygen in the reaction tube and the solvent, and allow the reaction to proceed at 110°C and nitrogen atmosphere for 17h. After the reaction is completed, quickly cool to room temperature, dilute the reaction mixture with tetrahydrofuran, and then slowly pour it into a large amount of cold methanol for precipitation. After standing for 24h to allow the product PFSF6-Br to be fully precipitated, discard the supernatant to obtain a yellow solid. Finally, the product is dissolved in THF and dialysis bag (M W CO=3500) was dialyzed in deionized water for 72h to fully remove the impurities such as residual initiator, small molecule initiator, methanol, etc. in the product. After the dialysis, the product was placed in a dry and clean beaker, dried in a 50℃ oven for 24h to remove a large amount of water, and then placed in a 50℃ vacuum oven to dry overnight, and finally a pure product macromolecular initiator PFSF6-Br was obtained.
[0050] In a high vacuum reaction tube, 1.133 g (0.04 mmol) of PFSF6-Br, 0.006 g (0.04 mmol) of Cu(I)Br, 0.019 g (0.04 mmol) of bipy, and 3.157 g (10.375 mmol) of PFSC8 were weighed, mixed, and dissolved in 5 mL of xylene. Then, a dry ice-ethanol bath was used and the mixture was subjected to freeze-vacuum-melt-vacuum cycles for 3 times to fully remove the oxygen dissolved in the reaction tube and the solvent. The reaction was carried out at 110° C. under a nitrogen atmosphere for 17 h. Finally, a brown-yellow solid (PFSF6-b-PFSC8) was obtained, and the pure product was obtained after purification.
[0051] Example 2
[0052] PFS 5.816g (30mmol), perfluorobutyl ethanol 5.282g (20mmol) and NaH 0.528g (22mmol) were added to a three-necked flask, mixed and dissolved in 60mL THF, and then the reaction was carried out at 0°C and N2 atmosphere for 19h. After the reaction was completed, the obtained reaction mixture was concentrated to remove the solvent, then washed with ice water, extracted with methyl tert-butyl ether, and the water was removed with anhydrous sodium sulfate. After being spin-dried, it was placed in a vacuum oven to dry for 2h, and finally a light yellow oily liquid was obtained, which was PFSF4.
[0053] The same synthesis steps were adopted, except that perfluorohexylethanol was replaced with 2.604 g (20 mmol) of n-octanol as feed material to obtain a light yellow oily liquid, which was PFSC8.
[0054] In a high vacuum reaction tube, add PFSF4 4.754g (10.80mmol), PhEBr 0.126g (0.68mmol), Cu(I)Br 0.097g (0.68mmol) and bipy 0.319g (2.04mmol), mix and dissolve in 5mL xylene. Then use a dry ice-ethanol bath, freeze-vacuum-melt-vacuum cycle 3 times, fully eliminate the dissolved oxygen in the reaction tube and the solvent, and allow the reaction to proceed at 110°C and nitrogen atmosphere for 17h. After the reaction is completed, quickly cool to room temperature, dilute the reaction mixture with tetrahydrofuran, and then slowly pour it into a large amount of cold methanol for precipitation. After standing for 24h to allow the product PFSF4-Br to be fully precipitated, discard the supernatant to obtain a yellow solid. Finally, the product is dissolved in THF and dialysis bag (M WCO=3500) was dialyzed in deionized water for 72h to fully remove the impurities such as residual initiator, small molecule initiator, methanol, etc. in the product. After the dialysis, the product was placed in a dry and clean beaker, dried in a 50℃ oven for 24h to remove a large amount of water, and then placed in a 50℃ vacuum oven to dry overnight, and finally a pure product macromolecular initiator PFSF4-Br was obtained.
[0055] In a high vacuum reaction tube, 0.903 g (0.04 mmol) of PFSF4-Br, 0.006 g (0.04 mmol) of Cu(I)Br, 0.019 g (0.04 mmol) of bipy, and 3.157 g (10.375 mmol) of PFSC8 were weighed, mixed, and dissolved in 5 mL of xylene. Then, a dry ice-ethanol bath was used and freeze-vacuum-melt-vacuum cycles were repeated three times to fully remove the oxygen dissolved in the reaction tube and the solvent. The reaction was carried out at 110° C. under a nitrogen atmosphere for 17 h. Finally, a brown-yellow solid (PFSF4-b-PFSC8) was obtained, and the pure product was obtained after purification.
[0056] Example 3
[0057] PFS 5.816g (30mmol), perfluorohexylethanol 7.286g (20mmol) and NaH 0.528g (22mmol) were added to a three-necked flask, mixed and dissolved in 60mL THF, and then the reaction was carried out at 0°C and N2 atmosphere for 19h. After the reaction was completed, the obtained reaction mixture was concentrated to remove the solvent, then washed with ice water, extracted with methyl tert-butyl ether, and the water was removed with anhydrous sodium sulfate. After being spin-dried, it was placed in a vacuum oven to dry for 2h, and finally a light yellow oily liquid was obtained, which was PFSF6.
[0058] The same synthesis steps were adopted, except that perfluorohexylethanol was replaced with 2.044 g (20 mmol) of n-hexanol as feed material to obtain a light yellow oily liquid, which was PFSC6.
[0059] In a high vacuum reaction tube, add PFSF6 5.813g (10.80mmol), PhEBr 0.126g (0.68mmol), Cu(I)Br 0.097g (0.68mmol) and bipy 0.319g (2.04mmol), mix and dissolve in 5mL xylene. Then use a dry ice-ethanol bath, freeze-vacuum-melt-vacuum cycle 3 times, fully eliminate the dissolved oxygen in the reaction tube and the solvent, and allow the reaction to proceed at 110°C and nitrogen atmosphere for 17h. After the reaction is completed, quickly cool to room temperature, dilute the reaction mixture with tetrahydrofuran, and then slowly pour it into a large amount of cold methanol for precipitation. After standing for 24h to allow the product PFSF6-Br to be fully precipitated, discard the supernatant to obtain a yellow solid. Finally, the product is dissolved in THF and dialysis bag (M W CO=3500) was dialyzed in deionized water for 72h to fully remove the impurities such as residual initiator, small molecule initiator, methanol, etc. in the product. After the dialysis, the product was placed in a dry and clean beaker, dried in a 50℃ oven for 24h to remove a large amount of water, and then placed in a 50℃ vacuum oven to dry overnight, and finally a pure product macromolecular initiator PFSF6-Br was obtained.
[0060] In a high vacuum reaction tube, PFSF6-Br 1.133 g (0.04 mmol), Cu(I)Br 0.006 g (0.04 mmol), bipy 0.019 g (0.04 mmol) and PFSC6 2.887 g (10.375 mmol) were weighed, mixed and dissolved in 5 mL of xylene, and then a dry ice-ethanol bath was used to perform freeze-vacuum-melt-vacuum cycles 3 times to fully remove the oxygen dissolved in the reaction tube and the solvent. The reaction was carried out at 110° C. under a nitrogen atmosphere for 17 h, and finally a brown-yellow solid (PFSF6-b-PFSC6) was obtained, which was purified to obtain a pure product.
[0061] <Test example>
[0062] 1. H NMR spectroscopy
[0063] The product prepared in Example 1-3 was structurally confirmed by H NMR spectrum test. Its H NMR spectrum is as follows: Figure 1 shown.
[0064] The results of H NMR spectrum showed that Examples 1-3 had a characteristic peak of -O-CH2- at 3.50-4.50 ppm, characteristic peaks of -CH3 and -CH2- at 0.75-1.40 ppm, and the -HC=CH2 peak (δ=5.65, 6.05, 6.60) disappeared, indicating that Examples 1 to 3 were successfully synthesized.
[0065] 2. Thermal stability and mechanical properties
[0066] The products prepared in Examples 1-3 were subjected to a thermogravimetric test to characterize their thermal stability, and then they were blended with polystyrene (PS) and hot-pressed (10% wt) to prepare thin sheets for contact angle and mechanical property tests.
[0067] The thermal decomposition temperatures of the products prepared in Examples 1-3 and the contact angles and mechanical properties of the blended materials are shown in Table 1. In Table 1, the comparative example is pure PS material.
[0068] Table 1 Thermal decomposition temperature of different fluorinated additives, contact angle and mechanical properties of blended materials
[0069]
[0070] The contact angle of the product prepared in Example 1-3 and PS in water / n-dodecane is shown in Figure 2 .
[0071] The test data of the above embodiments and comparative examples show that: the thermal decomposition temperature of the comparative examples is lower than that of embodiments 1-3, and the fluorinated block copolymers have good thermal stability; the water / n-dodecane contact angles of the comparative examples are lower than those of embodiments 1-3, indicating that the fluorinated block copolymers of the present application can greatly improve the hydrophobicity and oleophobicity of the material; the tensile strengths of the comparative examples are lower than those of embodiments 1-3, indicating that the fluorinated block copolymers of the present application have good compatibility.
[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A fluorinated block copolymer, characterized in that The structural formula is: R F CF3(CF2) m (CH2) n —, m is an odd number from 1 to 7, and n is an integer from 1 to 3; R C CH3(CH2) k —, k is an integer from 4 to 12; Where i:j = 0.5 ~2, and the value range of i and j is an integer from 10 to 100.
2. The fluorinated block copolymer according to claim 1, characterized in that R F CF3(CF2) m (CH2) n —, m is an odd number from 3 to 5, and n is an integer from 1 to 3; R C CH3(CH2) k —, k is an integer from 5 to 9; in i:j=1 ~1.5, the value range of i and j is an integer from 10 to 50.
3. The method for preparing a fluorinated block copolymer according to claim 1 or 2, characterized in that: The steps include: S1 In the reaction system, PFS reacts with perfluoro-substituted ethanol to obtain a first modified monomer, and PFS reacts with long-chain alkyl ethanol to obtain a second modified monomer; S2 In the reaction system, the first modified monomer is polymerized by atom transfer radical active polymerization to obtain a macromolecular initiator; The S3 macromolecular initiator and the second modified monomer are polymerized to obtain a fluorinated block polymer.
4. The method for preparing a fluorinated block copolymer according to claim 3, characterized in that: The reaction system includes a base, and the base includes at least one of sodium hydride, potassium hydride, and calcium hydride.
5. The method for preparing a fluorinated block copolymer according to claim 3, characterized in that: In S1, the reaction temperature is -10~30°C, and the reaction time is 3~30h.
6. The method for preparing a fluorinated block copolymer according to any one of claims 3 to 5, characterized in that: In S1, the first reaction monomer and the second reaction monomer were synthesized by affinity substitution at the 4-position of PFS; The molar ratio of PFS to perfluoro-substituted ethanol is 1 to 1.5:1; the molar ratio of PFS to long-chain alkyl ethanol is 1 to 1.5:
1.
7. The method for preparing a fluorinated block copolymer according to claim 3, characterized in that: In S2, the initiator is phenethyl bromide, and the catalyst is cuprous bromide and 2,2-bipyridine.
8. The method for preparing a fluorinated block copolymer according to claim 7, characterized in that: In S2, the molar ratio of phenethyl bromide, cuprous bromide and 2,2-bipyridine is 1: 1: 3; and / or the reaction temperature is 100-120° C., and the reaction time is 15-30 h.
9. The method for preparing a fluorinated block copolymer according to any one of claims 3 to 5, 7 and 8, characterized in that: S3 includes a catalyst, the catalyst is cuprous bromide and 2,2-bipyridine; the amount of cuprous bromide, 2,2-bipyridine, macromolecular initiator, and second modified monomer is 1: 1: 1~3: 200~350.
10. The method for preparing a fluorinated block copolymer according to claim 9, characterized in that: In S3, the reaction temperature is 100~120℃, and the reaction time is 15~30 h.
Citation Information
Patent Citations
Fluorine-containing two-block copolymer
JP5734406B1
Hydrophobic Flourinated Polymer Surfaces
US20090010870A1